Covıd 19: Measures Taken By Malaysıan Tertıary Englısh Educators In Overcomıng Challenges Durıng Emergency Remote Teachıng And Learnıng (ERTL) - Siti Mahirah Ab Wahab; Maslawati Mohamad (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The strike of the COVID-19 pandemic has forced the closures of most higher learning institutions around the world. Subsequently, the process of teaching and learning was being carried out online almost fully and this situation had yielded many challenges to tertiary English educators including those in Malaysia. Among the challenges faced were related to their technological skills, students’ participation, facilities, internet connection, and conducting assessments online. Subsequently, various measures were also taken by them to overcome the challenges in ensuring the continuity of the process of teaching and learning during this unprecedented situation. Thus, a multiple case study was conducted to explore the measures taken by nine English educators from three public universities in Malaysia, in overcoming the challenges they encountered during online learning throughout the COVID-19 pandemic. The data was collected through focused group interview sessions and individual open-ended responses for triangulation purposes. Based on the thematic analysis conducted, the findings disclosed that to overcome the challenges, educators had to improve their technological skills, find ways to increase students’ participation and conduct better online assessments. This study is believed could anticipate significant insights and guidance in planning and executing a meaningful ESL online teaching and learning experience for relevant parties, including the English educators, higher learning institutions, and the Ministry of Education especially during ERTL.